Ghost eaters : a novel - Chapman, Clay McLeod (Quirk Books, 2022)
"Erin and her friends from college, now in their mid-twenties, are shaken by the death of Silas, one of their own. They are plunged into a waking nightmare when they take a pill Silas learned of that allows them to see-and interact with-ghosts"--